Spleen and thymus metabolomics strategy to explore the immunoregulatory mechanism of total withanolides from the leaves of Datura metel L. on imiquimod‐induced psoriatic skin dermatitis in mice. (5th June 2020) - Cheng, Yangang; Liu, Yan; Tan, Jinyan; Sun, Yanping; Guan, Wei; Liu, Yuan; Yang, Bingyou; Kuang, Haixue
Abstract: Our previous work demonstrated that total withanolides of Datura metel L. leaves (TWD) exhibited excellent therapeutic effects on psoriasis. However, current knowledge of its mechanisms is incomplete. In this study, integrated spleen and thymus untargeted metabolomics were used to analyze the changes in endogenous metabolites underlying the immunosuppressive activity of TWD on psoriasis animal models induced by imiquimod. The results suggested that TWD treatment markedly attenuated imiquimod‐induced psoriasis and showed significant immunosuppressive activity as evidenced by decreased elevation index of spleen and thymus. Meanwhile, TWD significantly reversed the elevation of immunoregulatory factors, including IL‐10, IL‐17, IL‐22 and IL‐23. Multivariate trajectory analysis revealed that TWD treatment could restore the psoriasis‐disturbed spleen and thymus metabolite profiles towards the normal metabolic status. A total of 25 and 27 metabolites associated with the immunomodulatory effects for which levels changed markedly upon treatment have been identified in spleen and thymus, respectively. These differential metabolites were mainly involved in amino acid metabolism, nucleotide metabolism, fatty acid metabolism and lipid metabolism. Our investigation provided a holistic view of TWD for intervention in psoriasis through immunoregulation and provided further scientific information in vivo about a clinical value of TWD for psoriasis.